النشاط الجمعوي للطلبة الجزائريين الزيتونيين في تونس 1919م-1962م " نموذج عن بعض الجمعيات - ديدي حنان; بحة سعيدة; العوني مروى (جامعة الوادي - University of Eloued, 2025)
"تناولت هذه الدراسة موضوع النشاط الجمعوي الطلبة الزيتونيين في تونس نماذج لبعض الجمعيات ، ولقد تحوت إشكالية البحث في ما مدى مساهمة النشاط الجمعوي للطلبة الزيتونيين الجزائريين في تونس في بلورة نخبة مثقفة كان لها دور فعال في صنع الوعي الوطني الجزائري، حيث اعتمدنا لحل هذه الإشكالية ولدراسة الموضوع على المنهج التاريخي وكذا الوصفي والتحليلي ، ولقد قسمنا الموضوع إلى مقدمة ومدخل تمهيدي وثلاث فصول وخاتمة. أما عن المدخل التمهيدي فقد أبرزنا العلاقة بين الجزائر وتونس من القرن 16م الى الحماية الفرنسية 1881 أما الفصول فقد قسمناها الى ثلاثة ، الفصل الأول تحت عنوان البعثات العلمية نحو تونس ، والذي تضمن ثلاثة مباحث ، الأول بعنوان بعثة الطلبة الميزابيين، والثاني فقد إندرج تحنا عنوان بعثات جمعية العلماء المسلمين الجزائريين ، أما المبحث الثالث فقد أدرجنا فيه الرحلات العلمية الغير منتظمة نحو تونس ، أما الفصل الثاني بعنوان النشاط الجمعوي للطلبة الزيتونيين في تونس ، الذي تضمن ايضا ثلاث مباحث ، فالاول بعنوان تأسيس الجمعيات الطلابية الطلبة الزيتونيين ، والثاني يعنوان علاقة الجمعيات الجزائرية مع الجمعيات التونسية والأحزاب الوطنية ، أما المبحث الثالث فقد عنوناه بأبرز الطلبة التى كانت ناشطة في العمل الجمعوي، أما فيما يخص الفصل الثالث فقد تضمن نماذج عن بعض الجمعيات للطلبة الجزائريين الزيتونيين ، وقد أدرجناه تحث ثلاثة مباحث الأول تناول جمعية الطلبة الجزائريين الزيتونيين ، و الثاني جمعية الشباب السوفي الزيتونيين والمبحث الثالث بعنوان الاتحاد العام للطلبة المسلمين الجزائريين، وأخيرا خاتمة احتوت مجموعة النتائج التي تم التوصل إليها أن النشاط الجمعوي للطلبة الجزائريين الزيتونيين لم يكن مجرد نشاط طلابي عابر بل مثل دعامة أساسية في ترسيخ الوعي الوطني من خلال مشاركتهم الفعالة في جمعيات فكرية وثقافية ، مثل جمعية الطلبة الجزائريين الزيتونيين وجمعية الشباب السوفي الزيتوني. فقد ساهموا بشكل ملحوظ في دعم التعليم ونشر الفكر الإصلاحي، مما يجعل من تجربتهم نموذجا لكل الحركات الطلابية الطامحة إلى التغيير والإصلاح، حيث لعب النشاط الجمعوي والنخبة المثقفة الذي أفرزها هذا النشاط ، دورا محوريا في تنمية الوعي الوطني التحرري وكان تأسيس الأتحاد العام للطلبة المسلمين الجزائريين ، أبرز ما يعبر على هذا الوعي التحرري. "addressed the topic of the collective activity of Zaytouna students in Tunisia, models of some associations. The research problem revolved around the extent to which the collective activity of Algerian Zaytouna students in Tunisia contributed to the crystallization of an educated elite that played an effective role in shaping Algerian national awareness. To solve this problem and study the topic, we relied on the historical, descriptive and analytical method. We divided the topic into an introduction, a preliminary entrance. As for the introductory introduction, we highlighted the relationship between Algeria and Tunisia from the 16th century AD to the French protectorate in 1881. As for the chapters, we divided them into three. The first chapter is entitled “Scientific Missions to Tunisia,” which includes three topics. The first is entitled “The Mission of Mzabite Students,” and the second is entitled “The Missions of the Association of Algerian Muslim Scholars.” As for the third topic, we included irregular scientific trips to Tunisia. As for the second chapter, it is entitled “The Collective Activity of Zaytouna Students in Tunisia,” which also includes three topics. The first is entitled “The Establishment of Student Associations of Zaytouna Students,” and the second is entitled “The Relationship of Algerian Associations with Tunisian Associations and National Parties.” As for the third topic, we titled it “The Most Prominent Students Who Were Active in Collective Work.” As for the third chapter, it included examples of some associations of Algerian Zaytouna students, and its parts were included under three topics: the first dealt with the Association of Algerian Zaytouna Students, the second with the Association of Zaytouna Sovereign Youth, and the third with the title “The General Union of Algerian Muslim Students.” Finally, a conclusion that included a set of results that were reached, that the collective activity of Algerian Zaytouna students was not merely an activity My students were not only a passing student, but they were a fundamental pillar in consolidating national awareness through their active participation in intellectual and cultural associations, such as the Association of Algerian Zitouna Students and the Zitouna Soufi Youth Association. They contributed significantly to supporting education and spreading reformist thought, making their experience a model for all student movements aspiring to. And the educated elite
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: جمعية الطلبة الزيتونيين الجزائريين; النشاط الجمعوي; البعثات الميزابية; Mzab missions; community activity; Algerian Zitouna Students Association.